Is “Truthtelling” Decontextualized Online Still Reasonable? Restoring Context to Defamation Analysis in the Digital Age - Eltis, Karen (McGill Law Journal / Revue de droit de McGill, 2018)
This paper proposes to re-orient cyber defamation analysis towards a Civilian approach, whose hallmark flexibility and adaptability lends itself particularly well to the digital age. Indeed, harnessing the ordinary rules of negligence, and—in principle—foregoing defences, the Civilian construction is chiefly interested in the contextual reasonableness of the impugned expression (rather than in its truth or falsity strictly speaking), in contradistinction to its somewhat categorical Common Law counterpart. It is therefore recommended that defamation law evolve towards a “negligence standard” in common law parlance. Plainly put, this would require the plaintiff to make a showing of the contextual unreasonableness of impugned speech, an analysis which subsumes truthfulness and obviates the need for defences, this comporting with constitutional imperatives.Moreover and compounding the importance of revisiting the matter, “in a world where boundaries are porous and shifting” — and data is global, a cyber-publication in one jurisdiction may be read and reposted anywhere in the world, thereby potentially causing reputational harm transcending traditional or national parameters. Therefore, enforcing rights flowing from conduct originating outside of Canada increasingly preoccupies our courts who are gradually fearful of losing the ability to enforce local norms and policy or rectify domestically felt harm originating elsewhere. This preoccupation with “judicial helplessness” in Internet cases is evidenced by the notably liberalized jurisdiction test in Goldhar and Black inter alia and by two landmark cyber jurisdiction oriented cases handed down by the Supreme Court of Canada in 2017 alone. It is therefore essential to at least summarily address the jurisdiction question—if we are to have a true contextual understanding of cyber defamation as recommended herein.